PROMOTING DECENT WORK IN THE LOGISTICS SECTOR: ADDRESSING SDG 8 IN UZBEKISTAN - Abdumalik Erkinovich Soliyev; Samariddin Makhmudov (International Journal of Economic Integration and Regional Competitiveness, 2024)
This paper explores the challenges and opportunities associated with promoting decent work in Uzbekistan's logistics sector, aligning with Sustainable Development Goal (SDG) 8, which aims to promote sustained, inclusive, and sustainable economic growth, full and productive employment, and decent work for all. It examines the current state of the logistics labor market, highlighting issues such as working conditions, wages, and gender inequality. The paper also discusses strategies to improve labor standards, enhance worker rights, and foster a more inclusive workforce in the logistics sector. By implementing these strategies, Uzbekistan can ensure that the logistics sector contributes positively to economic growth and social well-being.